Acute Encephalitis Syndrome in Gorakhpur, Uttar Pradesh, 2016: Clinical and Laboratory Findings. Issue 11 (November 2018) - Mittal, Mahima; Bondre, Vijay; Murhekar, Manoj; Deval, Hirawati; Rose, Winsley; Verghese, Valsan Philip; Mittal, Mahim; Patil, Gajanan; Sabarinathan, Ramsamy; Vivian Thangaraj, Jeromie Wesley; Kanagasabai, Kaliaperumal; Prakash, John Antony Jude; et al.
Abstract : Background: Seasonal outbreaks of acute encephalitis syndrome (AES) with high fatality have been occurring in Gorakhpur, Uttar Pradesh, India, for several years. We conducted investigations during the 2016 outbreak to identify the etiology. Methods: We included 407 hospitalized AES patients with cerebrospinal fluid pleocytosis (>5 cells/mm 3 ) in our study. These patients were clinically examined; their blood and cerebrospinal fluid samples were collected and investigated for scrub typhus (ST), Japanese encephalitis virus (JEV), dengue virus and spotted fever group of Rickettsia by serology and/or polymerase chain reaction. Results: Of the 407 AES patients, 266 (65.4%), 42 (10.3%) and 29 (7.1%) were diagnosed to have ST, JEV and dengue infection, respectively. Four patients were diagnosed to have spotted fever group of Rickettsia infection. A significantly higher proportion of ST patients with AES had hepatomegaly, splenomegaly and facial edema. The common hematologic and biochemical abnormalities among ST-positive patients include thrombocytopenia, raised liver enzymes and bilirubin levels. The case fatality ratio was significantly higher among ST-negative AES patients (36.2% vs. 15.2%; P < 0.05). Conclusions: ST accounted for approximately two third of the AES case-patients. Efforts are required to identify the etiology of AES case-patients who are negative for ST, JEV and dengue fever.